Novel workflow for metagenomics and transcriptomics analysis of A.D. systems - Van Damme, Renaud (SLU/Dept. of Animal Environment and Health (until 231231), 2020)
The A.D. systems (anaerobic digestion), when used in biogas reactors, are an advanced ecological way to produce energy while treating waste. The majority of the microbial community of the reactor remains unknown to this day, due to the impossibility to culture most of the bacteria individually. Metagenomics and transcriptomics aim to discover those bacteria and understand the interactions within the community. HTS (high throughput sequencing) technology opens new possibilities in terms of length of the reads sequenced and accuracy. Sequencing done by Oxford Nanopore machines can produce long reads while having a slightly worse accuracy than other machines, where Illumina sequencing machines have a higher accuracy to the detriment of lengths. The two sequencing methods complement each other, and the hybrid assembly uses both long and short reads to create longer and more accurate contigs that can then be further analysed.